SIRT6 delays cellular senescence by promoting p27Kip1 ubiquitin-proteasome degradation - Zhao, Ganye (Aging (Albany NY), 2016)
Sirtuin6 (SIRT6) has been implicated as a key factor in aging and aging-related diseases. However, the role of SIRT6 in cellular senescence has not been fully understood. Here, we show that SIRT6 repressed the expression of p27(Kip1) (p27) in cellular senescence. The expression of SIRT6 was reduced during cellular senescence, whereas enforced SIRT6 expression promoted cell proliferation and antagonized cellular senescence. In addition, we demonstrated that SIRT6 promoted p27 degradation by proteasome and SIRT6 decreased the acetylation level and protein half-life of p27. p27 acetylation increased its protein stability. Furthermore, SIRT6 directly interacted with p27. Importantly, p27 was strongly acetylated and had a prolonged protein half-life with the reduction of SIRT6 when cells were senescent, compared with those young cells. Finally, SIRT6 markedly rescued senescence induced by p27. Our findings indicate that SIRT6 decreases p27 acetylation, leading to its degradation via ubiquitin-proteasome pathway and then delays cellular senescence.